FACTORS INCREASING THE EFFICIENCY OF ENVIRONMENTAL TOURISM SERVICES IN SAMARKAND REGION - Ahtamova M.E (Scholar Express Journals, 2021)
This article is devoted to the state and development of ecotourism in the Samarkand region. The factors that increase the efficiency of ecological tourism services in this area are also given. Based on the research carried out, proposals are presented that can help improve the quality of services provided in the ecotourism industry
Keywords: Ecotourism; strategy; factors; efficiency